Economic policy after the crash - Herbert Walther (Intervention. European Journal of Economics and Economic Policies, 2009)
First paragraph: The worldwide financial crisis, which started in the autumn 2007 at the climax of a bursting asset price bubble in the US, is still alive and with us, in spite of the tremendous, undoubtedly Keynesian and far reaching efforts of central banks and governments to mitigate its horrifying impact. Now, in the year 2009, heavy aftershocks are shattering the real economy throughout the world inducing the deepest recession in post-war history.
Keywords: 330